2019
DOI: 10.4103/ijo.ijo_710_18
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous endophthalmitis in children and adolescents: Case series and literature review

Abstract: Purpose: To study the clinical and microbiological profile, treatment modalities, and anatomical and functional outcomes among children and adolescents with endogenous endophthalmitis (EE) at a tertiary eye care centre in India. Methods: Medical records of subjects <18 years, presenting with EE from 1997 to 2007 were reviewed. Cases where the causative organism was identified were included. Treatment regimen included systemic antibiotics, vitrectomy, intravitreal antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Our study found that fungi accounted for half of the isolated organisms in endogenous endophthalmitis, similar to other studies in predominantly adult populations in China and the USA [28,29]. However, fungal infection was reported in 14.2-40% of pediatric endogenous endophthalmitis patients in India, although the sample size was small [6,20]. The higher rate of fungal infection in our study may be related to the small number of cases and geographic differences.…”
Section: Discussionsupporting
confidence: 86%
“…Our study found that fungi accounted for half of the isolated organisms in endogenous endophthalmitis, similar to other studies in predominantly adult populations in China and the USA [28,29]. However, fungal infection was reported in 14.2-40% of pediatric endogenous endophthalmitis patients in India, although the sample size was small [6,20]. The higher rate of fungal infection in our study may be related to the small number of cases and geographic differences.…”
Section: Discussionsupporting
confidence: 86%
“…Vitrectomy can mechanically remove infecting bacteria, toxins, cytokines, inflammatory cells, and membranes. Excellent visual outcomes following vitrectomy have previously been reported, especially in cases of fungal endogenous endophthalmitis [ 4 , 13 , 14 , 16 ]. However, many critically ill patients in this study were contraindicated for surgery due to multiple comorbidities, and 41.4% of eyes received at least one injection prior to the vitrectomy or evisceration/enucleation.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare, but sight-threatening, condition characterized by severe inflammation of the intraocular spaces. This condition is usually caused by hematogenous spread of organisms from a distant source through the blood-ocular barrier; it is associated with underlying factors such as diabetes mellitus, indwelling catheters, malnourishment, immunocompromised hosts, and intravenous drug abuse [ 1 4 ]. Clinical course of the condition is typically acute with rapid progression, requiring prompt diagnosis and management to preserve acceptable vision.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations